A Problem-Based Online Tutorial for Strengthening Pedagogical Reasoning in Distance Physics Teacher Education - Widiasih, Widiasih; Ismail, Ismail; Aprianti, Rika; Zakirman, Zakirman; Chaw, Ei Phyu (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2026)
Distance education requires instructional designs that promote meaningful interaction, independent learning, and authentic problem solving, particularly in physics teacher education where students must connect pedagogical concepts with real instructional practice. This study developed and evaluated the initial feasibility of a Problem-Based Learning (PBL)-based online tutorial for the Physics Learning Strategy course in a distance education setting. An adapted four-stage Research and Development model guided the processes of needs analysis, instructional design, expert validation, prototype development, limited implementation, and formative revision. Data were collected through expert validation sheets and student response questionnaires addressing tutorial quality, PBL organization, learning materials, language clarity, platform functionality, and collaborative learning support. The findings indicate that the tutorial demonstrated strong pedagogical and technical feasibility and was positively perceived by students during the initial implementation. Participants particularly appreciated the accessibility of the learning platform, the organization of learning materials, and the functionality of online features. Nevertheless, collaborative discussion and the implementation of problem-based learning stages remained the primary areas requiring refinement. These findings suggest that well-designed online tutorials can provide structured opportunities for pedagogical reasoning, collaborative inquiry, and reflective learning in distance physics teacher education. The study contributes a course-specific instructional framework that can inform the design of more interactive and pedagogically grounded online tutorials for higher education.